The nature of coxofemoral joint pathology across family Canidae. Issue 9 (7th December 2021) - Lawler, Dennis; Tangredi, Basil; Becker, Julia; Widga, Christopher; Etnier, Michael; Martin, Terrance; Schulz, Kurt; Kohn, Luci
Abstract: We evaluated coxofemoral joints from museum specimens of: Vulpes lagopus ; Vulpes vulpes ; Vulpes velox ; Nyctereutes procyonoides ; Urocyon cinereoargenteus ; Aenocyon [ Canis ] dirus ; Canis latrans ; Canis lupus lupus ; Canis lupus familiaris ; C. l. familiaris  ×  latrans ; and Canis dingo . Acetabular components included: fossa; articular surface; medial and lateral articular margins; and periarticular surfaces. Acetabular components variably revealed: osteophyte‐like features; varying appearance of articular margin rims (especially contour changes); rough bone surfaces (especially fossa and articular surface); and surface wear. Proximal femoral components included: articular surface; articular margin; periarticular surfaces; and joint capsule attachment. Femoral components variably revealed: rough bone surface; bone loss; articular margin osteophyte‐like features; caudal post‐developmental mineralized prominence; and enthesophytes along the joint capsule attachment. Non‐metric multidimensional scaling was used to analyze right–left asymmetric relationships between observed traits, across taxa. Significantly different acetabular trait asymmetry involved only C. latrans — C. l. familiaris ; V. vulpes — N. procyonoides, and U. cinereoargenteus — N. procyonoides . There were no significant lateralized differences in proximal femoral traits involving modern canids, ancient and modern C. l. familiaris, or modern vulpines. Thus, the observations were strongly bilateral. We hypothesized high similarity of traits across taxa. The data confirm the hypothesis and strongly suggest broad and deep morphological and mechanistic conservation that almost certainly pre‐existed (at least) all modern canids. Further zoological studies are needed to evaluate phylogenic implications in greater detail.